Analysis of miRNA-199-5p expression levels in serum samples of patients with lumbar disc degeneration: miRNA-199-5p in lumbar disc degeneration - Akdeniz, Fatma Tuba; Barut, Zerrin (Cellular and Molecular Biology, 2023)
Lumbar disc degeneration is a condition caused by damage to the disc due to various causes, which results in disc material coming out of the disc space. MicroRNAs are small, non-coding RNAs that play a role in the regulation of gene expression by binding to mRNA. MiRNA-199 has previously been studied in the context of intervertebral disc degeneration, and its role in the disease has been reported. The purpose of this study was to look into the role of miRNA 199 in Lumbar Disc Degeneration. This study included 26 patients with Lumbar Disc Degeneration who were admitted to the Neurosurgery Clinic at Yeditepe University Hospital and 26 completely healthy volunteer controls. After isolating microRNA from control and patient sera, was converted into cDNA, concentration measurements were taken, and PCR was used to analyze miRNA-199 expression. miRNA-199-5p expression levels were found to be statistically significantly higher in patients than in controls (P = 0.024). miRNA-199-5p Delta CT levels were also evaluated by ROC analysis (p = 0.014). miRNA-199-5p may be a candidate for a biomarker believed to play a role in disease prognosis in patients with Lumbar Disc Degeneration.